Escalamiento de un fotobiorreactor a nivel piloto para la producción de biomasa (2017)
Photobioreactor scaling implies that an intrinsic relationship between the design parameters and physiology of the organism determines an appropriate system operation. In this study, the model allows to evaluate the influence of light parameter into the growth of the microalgae Chlorella vulgaris as the diameter of the reactor increases, for an airlift FBR, with the aim of obtaining the highest biomass productivity from a low initial concentration. The model allowed a scaling from 7 to 50.2 liters with an increment of about 100 % in its production rate.